PENGARUH PROPORSI DIREKSI WANITA TERHADAP NILAI PERUSAHAAN TBK DI BEI PERIODE 2017-2021 - Muliawati; Cynthia Leonita; Catharina Tan Lian Soei (Universitas Katolik Parahyangan, 2025)
Amidst the increasing issue of gender equality among the general public, similar issues are also occurring in various companies regarding the position of women on the board of directors. Several previous studies have shown that women, with their cautious, risk-averse, and people-oriented characteristics, are able to make more mature and measured decisions, thus positively influencing company performance and value. However, previous research results do not always indicate that female directors have a positive influence on company value. Therefore, the purpose of this study is to determine whether there is an influence between the proportion of female directors and the value of companies listed on the Indonesia Stock Exchange (IDX) in 2017-2021. The research method is quantitative with a causality approach. Testing was conducted on sample of 150 companies. The dependent variable is company value, measured by the Tobin's Q ratio; the independent variable is the proportion of female directors; and there are two control variables: return on assets and financial leverage. The results show that the proportion of female directors influences company value, but the ability of the variable to explain variability of company value is very small.